Global Research Trends in Family Farming: A Bibliometric Insight - Suman, Swati; Prusty, Ajay Kumar; Deb, Atanu; Kumari, Alka (Indian Journal of Extension Education, 2025)
Family farming is considered as most sustainable form of agriculture, which is accepted worldwide. It is integral to food production, rural livelihood and cultural heritage. The concept of family farming changed significantly over time. The study utilizes the bibliometric analysis approach to examine the dynamic concept of family farming in the agricultural sector over the decade. The data is extracted from the Scopus database from 2015-2024 and analysed using bibliometric tools such as R Studio and VOSviewer. The study presents a thorough and measurable evaluation of the contributions from different countries, keyword frequencies and research trends with thematic evolution, offering a more empirical knowledge of the subject. The study investigates that the research has increasingly emphasized integrated and sustainable practices such as agroecology, gender role in farming and rural development policies. This shift reflects a growing recognition of family farming’s role in promoting sustainable agriculture, addressing global challenges and shaping a food-secure future for generations to come. To advance this crucial area of research, researchers, policymakers, and family farmers themselves must continue to work together.